Levando a sério a palhaçada: um estudo da natureza ambivalente do riso - Fernanda Moreto Fernandes (2011)
This dissertation intends to discuss the laughing and how it acts in our value questioning process. For that, I elected the clown, its agent per excellence, as the privileged character for the process understanding, once the clown provokes the laughing precisely in the inversion of the normativeness. We will discuss, besides that, the laughing in its sociohistorical context and anthropological point-of-view, referring to the buffoon and the jester for understanding how these characters contributed to the clown's acting and formation.